Identification And Assessment Of Pigmented Bacterial Isolates From Sea Cucumbers For Antibacterial Activity - Fatin Najihah Binti Muhammad Lutfi
Sea cucumber is one of the most commercialized seafood products in Asia, including Malaysia, and its consumption has recently increased with recognition of its health beneficial values. This marine invertebrate is surrounded by microbial communities that may provide defence against pathogens and, in turn, the symbiotic relationship could be a source of bioactive compounds. Many research on marine invertebrate-associated bacteria have been carried out, yet limited studies have documented on bacteria from various body parts of sea cucumbers in Malaysia seawaters, specifically on pigmented bacteria. In this study, eight sea cucumbers were collected from Pangkor Island, Perak, and Manukan Island, Sabah, and the specimens were identified as two H. leucospilota, three H. atra, and one each of H. edulis, H. hilla and B. vitiensis. A total of 115 bacterial samples were isolated from various body parts of the sea cucumbers, surrounding sediments and seawaters, and 58 bacterial strains were successfully identified using 16S rRNA gene amplification, DNA sequencing and phylogenetic analysis. Bacteria from the genera Vibrio and Bacillus are the most affiliated with sea cucumber from Pangkor Island and Manukan Island, respectively. Other bacterial strains belong to the genera Acinetobacteria, Staphylococcus, Pseudomonas, Paracoccus, Microbacterium, Brevundinomas, Exiguobacterium and Stenotrophomonas. Phylogenetic analysis revealed that isolates were assigned to three primary cluster consisting of Proteobacteria, Firmicutes and Actinobacteria phylum. Bacterial isolates that showed pigmentation were selected for UV-Vis spectrophotmetry analysis and antibacterial screening using disk diffusion method. The absorbance spectra of crude methanolic extract of Pseudomonas sp. PMCC1 suggested potential phenazine-based pigments, while those from Staphylococcus sp. PMDP, Microbacterium sp. PMCT1 and Acinetobacteria sp. PMDS1 resembling carotenoid pigments. However, more studies are needed to confirm these pigments. Four pigmented bacterial strains exhibited antibacterial activity against at least one pathogenic bacterium, with Pseudomonas sp. PMCC1 showed inhibition to all five tested bacteria, ranging from 13 to 22 mm. This study suggests that the bacteria isolated from sea cucumbers may have great potential in the discovery of useful bioactive compounds. Therefore, further studies are needed to explore this vast pool of bacterial isolates, especially the pigment-producing bacteria and to determine their biotechnological potentiality.